STATEMENT AND IMPLEMENTATION OF GOALS OF THE POLITICAL STRATEGY IS THE BASIS OF EFFECTIVE PUBLIC ADMINISTRATION - Okhotsky, Evgeny; Vorontsov, Sergey; Ponedelkov, Alexander; Mamychev, Alexey; Frolov, Sergey (Revista Inclusiones, 2019)
In the practice of public administration, politicians and managers at various levels of the state apparatus are inevitably faced with the problem of improving the efficiency of activities while striving to achieve the planned result at a lower cost. A combination of efficiency and effectiveness is possible and necessary to achieve the objectives of the various structural units within public administration. However, it should be recognized that the simplicity and speed in achieving performance goals leads to such practical situations where the heads of public services achieve results at the expense of effective activities in relation to the achievement of management goals. In this regard, it is important to identify and analyse those components of leadership activities and conditions that can significantly improve the effectiveness of public administration at different levels and in different political and socio-economic contexts. The scientific and methodological basis of the study is formed by the dialectical-materialistic concept of scientific knowledge, a set of General scientific and special methods of analysis of political, legal, economic, social, moral and managerial aspects of the effectiveness of the state strategy. The main conclusion: management decisions and measures for their effective implementation should be politically, legally and economically wellgrounded, should be targeted, implemented systematically and continuously, organically combined with consolidated actions on a global scale. The key to success is scientific validity, professionalism, responsibility, openness and constructiveness.